Kinect-Based Sliding Mode Control for Lynxmotion Robotic Arm. (27th July 2016) - Ben Abdallah, Ismail; Bouteraa, Yassine; Rekik, Chokri
Abstract : Recently, the technological development of manipulator robot increases very quickly and provides a positive impact to human life. The implementation of the manipulator robot technology offers more efficiency and high performance for several human's tasks. In reality, efforts published in this context are focused on implementing control algorithms with already preprogrammed desired trajectories (passive robots case) or trajectory generation based on feedback sensors (active robots case). However, gesture based control robot can be considered as another channel of system control which is not widely discussed. This paper focuses on a Kinect-based real-time interactive control system implementation. Based on LabVIEW integrated development environment (IDE), a developed human-machine-interface (HMI) allows user to control in real time a Lynxmotion robotic arm. The Kinect software development kit (SDK) provides a tool to keep track of human body skeleton and abstract it into 3-dimensional coordinates. Therefore, the Kinect sensor is integrated into our control system to detect the different user joints coordinates. The Lynxmotion dynamic has been implemented in a real-time sliding mode control algorithm. The experimental results are carried out to test the effectiveness of the system, and the results verify the tracking ability, stability, and robustness.